The Theory And Empirics Of Exchange Rates. (World Scientific, 2009)
Exchange rate economics is an important field of investigation for academics, professionals and policy-makers. This book provides a comprehensive survey of the theory of and empirical evidence on the determination and effects of exchange rates. The exposition utilizes both diagrammatic and mathematical representations of the underlying models. The book is a comprehensive reference for those engaged in this field of research. Sample Chapter(s). Chapter 1: Why DoWe Study Exchange Rates? (214 KB). Contents: Why Do We Study Exchange Rates?; Exchange Rate Determination in the Mundell-Fleming Model.